Upaya peningkatan prestasi belajar matematika melalui strategi pembelajaran open ended - I Ketut Suka Buana (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2021)
This classroom action research was carried out aimed at determining the extent to which the application of open-ended learning strategies could improve mathematics learning achievement and completeness of class X MIPA 8 students of SMA Negeri 2 Tabanan semester 1 of the 2019/2020 academic year. To achieve this goal, an open-ended learning strategy was implemented for class X MIPA 8 SMA Negeri 2 Tabanan semester 1 of the 2019/2020 academic year consisting of 36 people. The object of research is the achievement of learning mathematics and student learning completeness. Student mathematics learning achievement data were collected using learning achievement tests. While the data on student learning completeness were obtained from the percentage of students who had reached the KKM or more (KKM score = 70). Furthermore, the data collected in this study were analyzed descriptively. Furthermore, the data collected in this study were analyzed descriptively. The results of this study indicate that after implementing the open-ended learning strategy, there was an increase in students' mathematics learning achievement, namely in cycle I with an average value of 71.32 and in cycle II it increased to 78.95. While the completeness of student learning in the first cycle amounted to 80.55% increased in the second cycle reached 88.89%. Before the action was carried out, the student's average score was 69.05 and the students' completeness in learning was 77.78%. Penelitian tindakan kelas ini dilaksanakan bertujuan untuk mengetahui sejauh mana penerapan strategi pembelajaran open ended dapat meningkatkan prestasi belajar matematika dan ketuntasan siswa kelas X MIPA 8 SMA Negeri 2 Tabanan semester 1 tahun pelajaran 2019/2020. Untuk mencapai tujuan tersebut, diimplementasikan strategi pembelajaran open ended terhadap siswa kelas X MIPA 8 SMA Negeri 2 Tabanan semester 1 tahun pelajaran 2019/2020 yang terdiri atas 36 orang. Objek penelitian adalah prestasi belajar matematika dan ketuntasan belajar siswa. Data prestasi belajar matematika siswa dikumpulkan menggunakan tes prestasi belajar. Sedangkan data tentang ketuntasan belajar siswa diperoleh dari persentase siswa yang telah mencapai KKM atau lebih (nilai KKM = 70). Selanjutnya data yang terkumpul dalam penelitian ini dianalisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa setelah diimplementasikan strategi pembelajaran open ended, terjadi peningkatan prestasi belajar matematika siswa yaitu pada siklus I dengan nilai rata-rata sebesar 71,32 dan pada siklus II meningkat menjadi 78,95. Sedangkan ketuntasan belajar siswa pada siklus I sebesar sebesar 80,55% meningkat pada siklus II mencapai 88,89%. Sebelum dilakukan tindakan nilai rata-rata siswa sebesar 69,05 dan ketuntasan belajar siswa sebesar 77,78%.